THE EXPLORATION OF THE CHALLENGES ENCOUNTERED BY ESTABLISHED SOUTH AFRICAN FEMALE ENTREPRENEURS RELATING TO COMPETENCIES FOR BUILDING BRANDS IN THE AFRO-LUXE GOODS AND SERVICES INDUSTRY - Aylett, Kimon (The IIE, 2019)
This study has brought forward the analysis of the challenges and successes that established female South African entrepreneurs have encountered through the formation of their brands in the industry of luxury goods and services. The global female presence in the entrepreneurship sphere is increasing dramatically. The phenomena of female entrepreneurship are still developing and hold little valid research that is able to prominently convey the thinking behind successfully established female South African entrepreneurs. This research study aims to decipher the common challenges and competencies that resonates most with established Afro-luxe female entrepreneurs. The theoretical foundation in the secondary data comprised of the Competency Approach and Dilemma Orientated Theory. The primary data was collected via semi-structured interviews. Interviews will allow the researcher to derive the meaning from several female Afro-luxe entrepreneurs of their lived experiences of certain phenomena that will be outlined in various associated themes of challenges and competencies. Significant findings relating to cutting-edge views and perspectives on modern challenges and competencies that can contribute to the overall understanding of the modern day established South African Afro-luxe female entrepreneur will be presented.
Keywords: Brand; Brand building; Entrepreneurship; Luxury brands; Female entrepreneurship